math

posted by .

How would the instructor come up with this answer?
1-1/5with a exponet of 2 = 96%

  • math -

    1 - (1/5)^2 = 96%
    1 - (1/25) = 96%
    (25/25) - (1/25) = 96%
    (24/25) = 96%
    0.96 = 96%
    (0.96) 100% = 96%
    96% = 96%

  • math -

    1-1/5with a exponet of 2 = 96%

    I'm not sure how to interpret your data. You can indicate an exponent by putting this symbol (^) before the exponent. This what I assume:

    1 - 1/5^2 = 1 - .2^2 = 1 - .04 = .96 = 96%

    However, from the way you stated your question, it could be:

    (1 - 1/5)^2 = (4/5)^2 = .8^2 = .64

    I hope this helps. Thanks for asking.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. Math

    I know if you type Alt + 253 it will give you an exponet. I was wondering if anyone knows how to type a radical symbol?
  2. Algebra 2

    Simplify Each Expression. Rationalize all denominators. Assume that all variables are positive. 3 times the square root of 11x^3y (the three is an exponet) over -2 times the square root of 12x^4y (the 4 is an exponet)
  3. Math

    Give the numerical coeffiecent of -6m exponet 2
  4. Math

    1. A very magical teacher had a student select a two-digit number between 50 and 100 and write it on the board out of view of the instructor. Next, the student was asked to add 76 to the number, producing a three-digit sum. If the …
  5. Math

    Can you please explain this to me. The problem is 7/16 - 3/20 First I have to find the common denominator which would be 80 How does the 7/16 become 35/80 (where does the 35 come from) How does the 3/20 become a 12/80 (Where does the …
  6. math exam tommrow review

    (2*4) with a exponet of 2 ------ 7+3 with a exponet of 2
  7. math

    answer these or you don't have to just need some help?
  8. Math

    Which exponet makes the statement true? 1/5^9=5^?
  9. Math

    What are the coefficients in the expression -8y(exponet 2) + 12x + 5y+7?
  10. Math

    Elizabeth claims that she has proven that 7=5with the following: 7(a+b)-5(a+b)=7c-5c 7a+7b-5a-5b=7c-5c 7a+7b-7c=5a+5b-5c 7(a+b-c)/(a+b-c) = 5(a+b-c)/(a+b-c) 7=5 1.) Explain why this is an invalid proof.

More Similar Questions